2012
DOI: 10.1186/1471-2458-12-601
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices among people with chronic hepatitis B attending a hepatology clinic in Malaysia: A cross sectional study

Abstract: BackgroundHepatitis B (HBV) is the leading cause of cirrhosis and hepatocellular carcinoma worldwide. This study assessed the knowledge, attitudes and practices of people with chronic HBV and the associated factors.MethodsThis cross-sectional study was conducted at an outpatient adult hepatology clinic at a tertiary hospital in Kuala Lumpur. A self-administered questionnaire was administered on a one-to-one basis to assess knowledge, attitudes, and lifestyle practices of people with chronic HBV.ResultsThe resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
68
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 27 publications
15
68
3
Order By: Relevance
“…While hepatitis knowledge score was very low (0.26) among old age group of the respondents. These results are similar to the findings of Mohamed et al (2012). The educated people had high knowledge about hepatitis disease as reported by Haq et al (2012) and Adoba et al (2015).…”
Section: Resultssupporting
confidence: 91%
“…While hepatitis knowledge score was very low (0.26) among old age group of the respondents. These results are similar to the findings of Mohamed et al (2012). The educated people had high knowledge about hepatitis disease as reported by Haq et al (2012) and Adoba et al (2015).…”
Section: Resultssupporting
confidence: 91%
“…Mohammad R et al found in their study in Malaysia that majority were aware that the clinical consequences of HBV infection include inflammation of the liver (81.6%), liver failure (78.5%) and liver cancer (85.1%). 22 These two results vary possibly due to different educational background of these two countries. Chi-square test revealed that there was statistical significant association between education status and history of taking HBV vaccine (p=0.000).…”
Section: Resultsmentioning
confidence: 98%
“…Chinese people in China and in the USA were the most studied groups. [242526272829303132333435] The participants were HBV-infected patients, members of the general community, health-care providers, or community leaders [Tables 1 and 2]. All participants were adults.…”
Section: Resultsmentioning
confidence: 99%